Economic viability and cost analysis for photocatalytic membranes - Yusuf Olabode, Raji; Khairul Anwar, Mohamad Said (4 Elsevier Ltd., 2024)
The economic analysis and cost evaluation of membranes development are very important indices to test the viability and acceptability, in particular, photocatalytic ceramic membranes. The cost evaluation/viability is a procedure for assessing the economic, social, environmental, and financial impact of the proposed capital of any design [13]. All the impacts associated with project development are identified and, where possible, costs and benefits are valued in monetary terms so that the design selected by the government, organization, or individuals will provide the maximum net profit [1]. The overall cost of an asset across its life cycle, including original capital cost, maintenance costs, operating costs, and the asset’s residual value at the end of its life, can be calculated using the life cycle cost (LCC) method [46]